Effect of fish protein hydrolysate-enriched mocaf biscuits on fecal short-chain fatty acid levels in obese adults - Putri Indah Nurmalasari; Etika Ratna Noer; Ahmad Ni'matullah Al-Baarri (AcTion: Aceh Nutrition Journal, 2026)
Obesity is linked to dietary patterns that influence gut microbiota balance and short-chain fatty acid (SCFA) production, which regulate energy metabolism and appetite. However, evidence regarding the effects of fish protein hydrolysates (FPH) on SCFA levels in humans remains limited. This study evaluated the effects of FPH-based mocaf biscuits on fecal SCFA levels in obese adult participants. A two-stage design was applied: (1) formulation and evaluation of four biscuit variants (F0–F3) and (2) a randomized controlled post-only trial involving 30 obese participants aged 20–50 years from Semarang, Indonesia. Participants consumed 60 g of biscuits daily for four weeks, along with a 1500 kcal/day diet. Anthropometric, dietary, and fecal SCFA data were collected, and statistical analyses were performed using Shapiro–Wilk, Mann–Whitney, and paired t-tests (α = 0.05). The F2 biscuits had the highest protein content (4.66%) and sensory acceptance (p<0.05). Baseline SCFA levels were comparable between the groups, and post-intervention differences were not significant (p=0.071), although the treatment group showed a slight decrease in visceral fat (p=0.089) and waist circumference (p=0.094). In conclusion, FPH-enriched mocaf biscuits improved protein quality and acceptability but did not significantly alter fecal SCFA levels in obese adults.